Ismuba Learning Problems and Solutions During Pandemic in Elementary School - Mochammad Faris Ainun Habibi; Anita Puji Astuti (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2021)
The Covid-19 pandemic is something that needs to be considered, because Covid-19 is an event that will endanger human safety, including health and human life itself, with the implementation of physical distancing, the government has limited student communication distances to prevent transmission of the corona virus. This pandemic is also a problem in the field of education because the interaction and communication of a teacher with students is very limited. Teachers cannot speak face to face directly to students and vice versa because of the covid-19 pandemic. Now only interact and communicate through online learning or can be known as online learning. Many problems occur in online learning, but there are also many solutions to reduce a problem. Online learning is not only conveying material to students, but also instilling a religiosity in maintaining the character of students so that they remain in Islamic values. From the research research that has been obtained by researchers using qualitative methods and questions and answers about the problems and solutions for ismuba learning here, it shows that the problems of online learning are currently proven that 77% of students at the Creative School of Muhammadiyah Elementary School 2 Tulangan can understand easily. Of course, there are many aspects that support other than the government and educational institutions, but parents really need to support teaching and learning activities for students.